IMPROVED PERFORMANCE OF THE BOLT-CONNECTED SHEAR LINK WITH FLUSH END PLATE DUE TO CYCLIC LOADING - NOVAN (NIM 25006002), ANDRE
The performance of bolt-connected shear link with flush type of end plate in eccentric brace steel frame (EBF) has some disadvantages compared with welded type connection. Kinking of end plate and excessive bolt elongation, decrease energy dissipation as shown by pinching in hysteretic curve. This study aims to improve the performance of bolt connected by using large diameter of High Strength Bolt (HSB) and thicker end plate. Experimental work has been carried out on two specimens of shear link. Both specimens have been designed comply to the specification for structural steel building, as well as to the capacity design concept for all of element and connection part outside the link. The second specimen was strengthened by extended flange at each link end that called Side Extended Plate (SEP). Cyclic loading test was carried out on loading frame with displacement control procedure. The test result showed both specimens performed improvement in strength, stiffness, ductility and energy dissipation capacity compared with the result of previous study. Furthermore, the second specimen (SEP) showed improved performance compared with first specimen i.e. 11,7% increase in ultimate load capacity, 28,6% increase in ductility and 88,4% increase in total energy dissipation. The result also showed that no significant difference occurs in the elastic performance on both specimens. The plastic rotation capacity on both specimen are Yup1=0,13 rad and Yup2=0,18 rad, respectively. This shows that both bolt-connected link specimens could be used in EBF steel structure as stated in Seismic Provision for Structural Steel Building (AISC-2005).